Objective adherence to dental device versus positive airway pressure treatment in adults with obstructive sleep apnea. (30th November 2020) - Xu, Liyue; Xie, Dawei; Griffin, Kara S.; Staley, Bethany; Wang, Ying; Nichols, Deborah A.; Benca, Ruth M.; Pack, Allan I.; Redline, Susan; Walsh, James K.; Kushida, Clete A.; Kuna, Samuel T.
Abstract: Although mandibular advancement device (MAD) treatment of adults with obstructive sleep apnea (OSA) is generally less efficacious than positive airway pressure (PAP), the two treatments are associated, with similar clinical outcomes. As a sub‐analysis of a randomized trial comparing the effect of MAD versus PAP on blood pressure, this study compared objectively measured adherence to MAD versus PAP treatment in adults with OSA. Adults with OSA (age 54.1 ± 11.2 [standard deviation] years, 71.1% male, apnea–hypopnea index 31.6 ± 22.7 events/h) were randomized to MAD ( n = 89) or PAP ( n = 91) treatment for 3–6 months. Objective adherence was assessed with a thermal sensor embedded in the MAD and a pressure sensor in the PAP unit. In a per protocol analysis, no difference was observed in average daily hours of use over all days in participants on MAD ( n = 35, 4.4 ± 2.9 h) versus PAP ( n = 51, 4.7 ± 1.6 h, p = .597) treatment when days with missing adherence data were included as no use. MAD was used on a lower percentage of days (62.5 ± 36.4% versus 79.9 ± 19.8%, p = .047), but with greater average daily hours of use on days used (6.4 ± 1.9 h versus 5.7 ± 1.2 h, p = .013). Average daily hours of use in the first week were associated with long‐term adherence to MAD ( p < .0001) and PAP ( p = .0009) treatment. Similar results were obtained when excluding days with missing adherence data. In conclusion, no significant difference was observed in objectively measured average daily hours of MAD and PAP adherence in adults with OSA, despite differences in the patterns of use. MAD adherence in the first week predicted long‐term use.